TRANSFORMATION OF EDUCATION THROUGH IT-BASED LEARNING MEDIA IN GEOGRAPHY SUBJECTS ON NATURAL DISASTERS: TRANSFORMASI PENDIDIKAN MELALUI MEDIA PEMBELAJARAN BERBASIS TI PADA MATA PELAJARAN GEOGRAFI POKOK BAHASAN BENCANA ALAM - Asgar; Razilu, Zila; Darman (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2025)
This study aims to evaluate the use of information technology (IT)-based learning media in teaching geography on natural disasters at SMAN 13 Konawe Selatan. Observation and questionnaires were used to identify teaching practices applied by teachers and students' perceptions of IT-based media. The results showed that teachers had utilized technology such as PowerPoint and projectors to help deliver materials. However, using more interactive media, such as animated videos, is still rare. Analysis of the student engagement questionnaire revealed that most students felt more engaged in IT-based learning, with 40.4% agreeing and 39.8% strongly agreeing that this media increased their engagement. Although these results show positive potential, limitations in teachers' skills to develop and implement IT media are a significant challenge. This research emphasizes the need for adequate training and facility support for teachers to optimize the use of technology in learning. The conclusion of this study confirms that IT-based learning media can improve student engagement and understanding, but additional support is needed for more effective implementation. The findings have important implications for developing learning strategies that are more interactive and relevant to the needs of modern education.